An Analysis of the Perception of Growth Mindset in Relation to Parenting Styles Among Elementary School Teachers - I Gede Krisna Oviantika; Putu Nanci Riastini; Ni Made Dainivitri Sinta Sari (Mimbar Ilmu, 2026)
Teachers’ growth mindset shows variation that is not yet optimal, where some teachers do not fully believe that abilities can be developed through effort, experience, and continuous learning, resulting in a tendency toward a fixed mindset among certain individuals. This condition is assumed to be influenced by both internal and external factors, one of which is family parenting style experienced during childhood. This study aims to analyze and compare teachers’ perceptions of their growth mindset based on the parenting style they experienced from their parents. This research uses a descriptive quantitative approach with 48 teachers selected through a total sampling technique. Data were collected using a closed-ended questionnaire that had been tested for validity and reliability, and then analyzed using descriptive statistics. The results indicate that teachers’ growth mindset is predominantly in the moderate to high category, with a small proportion in the strong and fixed mindset categories. In terms of parenting style, most respondents were raised under an authoritative parenting style, while a small number experienced permissive parenting, and no authoritarian parenting was found. The comparison results show that authoritative parenting is associated with a more positive growth mindset. Overall, this study concludes that authoritative parenting plays an important role in fostering teachers’ growth mindset through balanced support and guidance. The implication of this study is that the development of growth mindset should consider family factors as well as supportive educational environments that encourage reflection, resilience, and lifelong learning.